The PE-PPE domain in mycobacterium reveals a serine α/β hydrolase fold and function: an in-silico analysis. - Rafiya Sultana (Public Library of Science (PLoS), 2011)
The PE and PPE proteins first reported in the genome sequence of Mycobacterium tuberculosis strain H37Rv are now identified in all mycobacterial species. The PE-PPE domain (Pfam ID: PF08237) is a 225 amino acid residue conserved region located towards the C-terminus of some PE and PPE proteins and hypothetical proteins. Our in-silico sequence analysis revealed that this domain is present in all Mycobacteria, some Rhodococcus and Nocardia farcinica genomes. This domain comprises a pentapeptide sequence motif GxSxG/S at the N-terminus and conserved amino acid residues Ser, Asp and His that constitute a catalytic triad characteristic of lipase, esterase and cutinase activity. The fold prediction and comparative modeling of the 3-D structure of the PE-PPE domain revealed a "serine α/β hydrolase" structure with a central β-sheet flanked by α-helices on either side. The structure comprises a lid insertion with a closed structure conformation and has a solvent inaccessible active site. The oxyanion hole that stabilizes the negative charge on the tetrahedral intermediate has been identified. Our findings add to the growing list of serine hydrolases in mycobacterium, which are essential for the maintenance of their impermeable cell wall and virulence. These results provide the directions for the design of experiments to establish the function of PE and PPE proteins.